High diagnostic yield of direct Sanger sequencing in the diagnosis of neuronal ceroid lipofuscinoses. Issue 1 (3rd September 2019) - Jilani, Abdulhakim; Matviychuk, Diana; Blaser, Susan; Dyack, Sarah; Mathieu, Jean; Prasad, Asuri N.; Prasad, Chitra; Kyriakopoulou, Lianna; Mercimek‐Andrews, Saadet
Abstract: Background: Neuronal ceroid lipofuscinoses are neurodegenerative disorders. To investigate the diagnostic yield of direct Sanger sequencing of the CLN genes, we reviewed Molecular Genetics Laboratory Database for molecular genetic test results of the CLN genes from a single clinical molecular diagnostic laboratory. Methods: We reviewed electronic patient charts. We used consent forms and Research Electronic Data Capture questionnaires for the patients from outside of our Institution. We reclassified all variants in the CLN genes. Results: Six hundred and ninety three individuals underwent the direct Sanger sequencing of the CLN genes for the diagnosis of neuronal ceroid lipofuscinoses. There were 343 symptomatic patients and 350 family members. Ninety‐one symptomatic patients had molecular genetic diagnosis of neuronal ceroid lipofuscinoses including CLN1 (PPT1) (n = 10), CLN2 ( TPP1 ) (n = 33), CLN3 (n = 17), CLN5 (n = 7), CLN6 (n = 10), CLN7 ( MFSD8 ) (n = 10), and CLN8 (n = 4) diseases. The diagnostic yield of direct Sanger sequencing of CLN genes was 27% in symptomatic patients. We report detailed clinical and investigation results of 33 NCL patients. Juvenile onset CLN1 ( PPT1 ) and adult onset CLN6 diseases were nonclassical phenotypes. Conclusion: In our study, the diagnostic yield of direct Sanger sequencing was close to diagnostic yield of whole exome sequencing. Developmental regression, cognitive decline, visual impairment and cerebral and/or cerebellar atrophy in brain MRI are significant clinical and neuroimaging denominators to include NCL in the differential diagnosis.